Wartime Experiences and Popular Support for Peace Agreements: Comparative Evidence from Three Cases. (October 2022) - Dyrstad, Karin; Binningsbø, Helga M.; Bakke, Kristin M.
Peace agreements are negotiated and signed by representatives of the government and the rebels, often after many years of violent conflict, but their ability to transform a war-torn society hinges on the approval of ordinary people. Yet we have little systematic knowledge of what ordinary people think of peace agreements in the long run. This study begins to fill that gap, drawing on a set of comparative public opinion surveys from Guatemala, Nepal, and Northern Ireland, three cases where long civil wars were ended by peace agreements. The peace agreements in these countries have strong popular support, though there is variation across specific provisions. Across these cases, our findings suggest that legacies of violence are not generally associated with long-term support for peace agreements. However, when we look at provisions that grant concessions to the rebels, there is some evidence of lasting legacies.